Tinjauan Kriminologis terhadap Tindak Pidana Pemerkosaan yang Dilakukan oleh Ayah terhadap Anak Kandung (Studi Kasus Putusan Pengadilan Negeri Batam Nomor: 774/PID.SUS/2017/PN BTM) - Eko Nurisman; Samuel Tan (Fakultas Hukum, Universitas Internasional Batam, 2019)
This thesis studies the criminological review of rape done by father towards biological children (study case no.774/Pid.sus.2014/PN.BTM) where in this study aims to find out three things, first to find out the factors that cause criminal measures rape acts committed by father against biological children, secondly to find out the application of criminal in decision no.774/Pid.sus/2017/PN.BTM about the rape of biological children, and thirdly to find out the efforts to deal with crime against rape committed by the father of the biological children.This thesis report is prepared using normative research methods while the data is obtained through secondary data. Then the data obtained were analyzed qualitatively so as to reveal the expected results and conclusions of the problem. In this thesis, the researcher finds that the main factor influencing the occurrence of rape of biological children is the opportunity that is obtained by the offender so that he can easily satisfy his lust desires, so that the perpetrator must obtain a criminal that is worthy and as fair as possible with the act that the perpetrator has committed against his child. Not only focused on criminal convictions, there are preventive measures that must be done so that these actions can be reduced even if they do not happen again such as instilling good and educative values ​​to the community and conducting socialization, seminars and counseling to the community.